Rince Preferences - Farmer, Roger E. A. (Quarterly Journal of Economics, 1990)
This paper presents a class of preferences that yield closed-form solutions to dynamic stochastic choice problems. These preferences are based on a set of axioms that were proposed by Kreps and Porteus. The Kreps-Porteus axioms allow one to separate an agent's attitudes to risk from his or her intertemporal elasticity of substitution. RINCE preferences have the properties of Risk Neutrality and Constant Elasticity of substitution.